In vitro expression of NLRP inflammasome-induced active Caspase-1 expression in normal human epidermal keratinocytes (NHEK) by various exogenous threats and subsequent inhibition by naturally derived ingredient blends - Gruber JV; Holtz R (Dove Medical Press, 2019)
James V Gruber,1 Robert Holtz21Research and Development, BotanicalsPlus, Little Falls, NJ 07424, USA; 2Research and Development, Bioinnovation Laboratories, Inc, Lakewood, CO 80235, USACorrespondence: James V GruberBotanicalsPlus, 163 East Main Street, Suite #273, Little Falls, NJ 07424, USAEmail VGruber@BotanicalsPlus.comBackground: The discovery of the nod-like receptor protein (NLRP) inflammasomes in 2002 has led to the rapid identification of these unique cellular proteins as key targets for studies on innate inflammation pathways. The NLRP inflammasomes have been shown to be expressed in normal human epidermal keratinocytes (NHEK) and human dermal fibroblasts (HDF). NLRP inflammasomes in keratinocytes are interesting as these skin cells are the first living cells in the skin to contact external exogenous threats such as UV energy, chemicals, physical trauma, and bacteria and viruses. Activation of the NLRP Inflammasomes by exogenous threats results in the release of active Caspase-1 (ACasp-1), a key protease enzyme, which targets inactive forms of IL-1β, IL-18 as well as IL-1α and IL-33.Purpose: This article discusses efforts to examine the release of active Caspase-1 from NHEKs activated by various exogenous threats including UVB energy, ATP, Nigericin and Urban Dust. The work further examines if, after inflammasome activation and Caspase-1 release, certain naturally derived botanical ingredients known to have anti-inflammatory effects can function to inhibit upregulation of active Caspase-1.Methods: NHEK were treated with various doses of UVB, ATP and Nigericin and with a single dose of Urban Dust. ACasp-1 expression was measured after 3 and 20 hours using the Promega Caspase Glo-1 bioluminescent assay. After confirmation that 60 mJ/cm2 of UVB and 5mM of ATP were effective to activate NHEK ACasp-1 release after 20 hrs, these conditions were employed to examine the influence of three botanical blends of ingredients on their ability to inhibit ACasp-1 expression.Results: Initial results demonstrate that NHEKs can be activated to release active Caspase-1 by ATP and UVB, but not by Nigericin or Urban Dust. In addition, it was unexpectedly found that, while ATP and UVB activated NHEKs, the release of ACasp-1-did not happen within the first 3 hours after exposure but did become significant after 20 hours. Additional results indicate that a blend of polysaccharides and two blends of antioxidants, one oil-soluble and the other water-soluble, known for their anti-inflammatory effects, can reduce expression of active Caspase-1 in activated NHEKs when applied extracellularly.Conclusion: Expression of NLRP activated release of ACasp-1 was found to be influenced by UVB and ATP but not by Nigericin or Urban Dust. The effects were also time dependent. Several botanical extract blends were found to reduce ACasp-1 expression in previously activated NHEKs. Links between these inflammatory effects and processes of cellular inflammaging are discussed.Keywords: inflammation, inflammasome, NLRP3, NLRP1, polysaccharide, antioxidant, Caspase-1